Columbite–Tantalite from Northern Scandinavia (Kaustinen, Kolmozero) Pegmatites: An Optical and Spectroscopic Properties - Miłosz Huber; Daniel Kamiński; Urszula Maciołek (Crystals, 2023)
LCT (lithium–cesium–tantalum) pegmatites from the Kaustinen and Kolmozero regions contain columbite–tantalite mineralization, which has been presented in this study. Crystal structure, Raman microscopy, and optical property analyses of these minerals were performed. As a result of the structural studies and micro-area analyses, it was determined that these minerals in the pegmatites in question constitute a solid solution with numerous Mn-Fe and Nb-Ta substitutions within a single crystal. The ratio between Mn-Fe and Nb-Ta can change from crystal to crystal, which makes it impossible to find precise stechiometry between these ions. The crystallization conditions of these minerals were also determined by studying the associations of other rock-forming minerals and accessory minerals in the discussed rocks.